Insulin treatment of maternal diabetes mellitus and respiratory outcome in late-preterm and term singletons. Issue 6 (2nd June 2015) - Becquet, Odile; El Khabbaz, Fares; Alberti, Corinne; Mohamed, Damir; Blachier, Audrey; Biran, Valérie; Sibony, Olivier; Baud, Olivier
Abstract : Objectives: While the incidence of diabetes mellitus (DM) during pregnancy has been steadily increasing in recent years, the link between gestational DM and respiratory outcome in neonates has not been definitely established. We asked the question whether DM status and its treatment during pregnancy could influence the risk of neonatal respiratory distress. Design: We studied in a large retrospective cohort the relationship between maternal DM status (non-DM, insulin-treated DM (IT-DM) and non-insulin-treated DM (NIT-DM)), and respiratory distress in term and near-term inborn singletons. Results: Among 18 095 singletons delivered at 34 weeks of gestation or later, 412 (2.3%) were admitted to the neonatal intensive care unit (NICU) for respiratory distress within the first hours of life. The incidence of NICU admission due to respiratory distress groups was 2.2%, 5.7% and 2.1% in the non-DM, IT-DM and NIT-DM groups, respectively. Insulin treatment of DM, together with several other perinatal factors, was associated with a significant increased risk for respiratory distress. Several markers of the severity of respiratory illness, including durations of mechanical ventilation and supplemental oxygen, and hypertrophic cardiomyopathy were also found increased following IT-DM as compared with NIT-DM. In a multivariate model, we found that IT-DM, but not NIT-DM, was significantly associated with respiratory distress independent of gestational age and caesarean section, with an incidence rate ratio of 1.44 (1.00–2.08). Conclusions: This study shows that the treatment of maternal DM with insulin during pregnancy is an independent risk factor for respiratory distress in term and near-term newborns.